Continuous extraction and concentration of secreted metabolites from engineered microbes using membrane technology. Issue 14 (25th May 2022) - Overmans, Sebastian; Ignacz, Gergo; Beke, Aron K.; Xu, Jiajie; Saikaly, Pascal E.; Szekely, Gyorgy; Lauersen, Kyle J.
Abstract : Light-driven engineered microalgal cultivation in photobioreactors coupled with membrane separations of secreted metabolites as next generation sustainable bio-processes. Abstract : Microalgal cultivation in photobioreactors and membrane separations are both considered sustainable processes. Here we explore their synergistic combination to extract and concentrate a heterologous sesquiterpenoid produced by engineered green algal cells. A hydrophobic hollow-fiber membrane contactor was used to allow interaction of culture broth and cells with a dodecane solvent phase to accumulate algal produced patchoulol. Subsequent continuous membrane extraction of patchoulol from dodecane enabled product concentration in a methanol stream as well as dodecane recovery for its reuse. A structure-based prediction using machine learning was employed to model a process whereby 100% patchoulol recovery from dodecane could be achieved with solvent-resistant nanofiltration membranes. Solvent consumption, E-factor, and economic sustainability were assessed and compared with existing patchoulol production processes. Our extraction and product purification process offers six- and two-orders of magnitude lower solvent consumption compared to synthetic production and thermal-based separation, respectively. Our proposed methodology is transferable to other microbial systems for the isolation of high-value isoprenoid and hydrocarbon products.